Biochar and carbon-negative technologies: exploring opportunities for climate change mitigation - Muhammad Ayaz; Sidra Tul Muntaha; Edita Baltrėnaitė-Gedienė; Zita Kriaučiūnienė (Biochar)
Abstract The study highlights the critical mechanistic data supporting the ecological restoration advantages of biochar (BC) and its role in sustainable environmental management. Recognizing the substantial influence of specific feedstock sources and pyrolysis parameters on BC efficacy, this research aims to address these gaps through an extensive investigation into the potential benefits of BC application in ecological restoration. The methodology involves a systematic exploration of effects of BC from latest literature on various aspects of agricultural sustainability, including its ability to support crop growth, improve nutrient bioavailability, facilitate co-composting, enhance consumption efficiency, and contribute to water quality restoration. The main results of the study reveal that BC usage results in a net negative carbon (C) footprint, mitigates heavy metal pollution, and enhances soil and ecosystem health. In bioenergy production, BC serves as a versatile resource for generating renewable energy, reducing waste, and facilitating C sequestration. Advanced BC techniques, such as tailored pyrolysis processes and activation methods, further enhance its effectiveness in ecosystem restoration and sustainable resource management. Furthermore, the research identifies deficiencies in current literature and proposes future research directions to advance understanding of BC application. Overall, the study underscores the importance of considering feedstock and pyrolysis variables in BC research and highlights the potential of BC to contribute to ecological sustainability. However, concerns regarding potential health implications for humans in agricultural contexts warrant further investigation and risk assessment to ensure safe and sustainable BC application. Graphical Abstract